Adverse Outcome Pathway on Androgen receptor agonism leading to male-biased sex ratio - Santana Rodriguez, Kelvin J.. (OECD Publishing, 2023)
This adverse outcome pathway links androgen receptor agonism in teleost fish during gonadogenesis to male-biased sexual differentiation and consequently, reduced population growth rate. Sex determination in teleost fishes is highly plastic; it can be genetically or environmentally influenced. Species with environmentally-based sex determination in particular can be very sensitive to exogenous chemicals during the period of differentiation. Exogenous hormones are of ecological concern because they have the potential to alter gonad development and sex differentiation. This AOP is referred to as AOP 376 in the Collaborative Adverse Outcome Pathway Wiki (AOP-Wiki)
Keywords: Environment